GATA2 regulates dendritic cell differentiation - Onodera, Koichi (Blood, 2016)
Dendritic cells (DCs) are critical immune response regulators; however, the mechanism of DC differentiation is not fully understood. Heterozygous germ line GATA2 mutations induce GATA2-deficiency syndrome, characterized by monocytopenia, a predisposition to myelodysplasia/acute myeloid leukemia, and a profoundly reduced DC population, which is associated with increased susceptibility to viral infections, impaired phagocytosis, and decreased cytokine production. To define the role of GATA2 in DC differentiation and function, we studied Gata2 conditional knockout and haploinsufficient mice. Gata2 conditional deficiency significantly reduced the DC count, whereas Gata2 haploinsufficiency did not affect this population. GATA2 was required for the in vitro generation of DCs from Lin(−)Sca-1(+)Kit(+) cells, common myeloid-restricted progenitors, and common dendritic cell precursors, but not common lymphoid-restricted progenitors or granulocyte-macrophage progenitors, suggesting that GATA2 functions in the myeloid pathway of DC differentiation. Moreover, expression profiling demonstrated reduced expression of myeloid-related genes, including mafb, and increased expression of T-lymphocyte–related genes, including Gata3 and Tcf7, in Gata2-deficient DC progenitors. In addition, GATA2 was found to bind an enhancer element 190-kb downstream region of Gata3, and a reporter assay exhibited significantly reduced luciferase activity after adding this enhancer region to the Gata3 promoter, which was recovered by GATA sequence deletion within Gata3 +190. These results suggest that GATA2 plays an important role in cell-fate specification toward the myeloid vs T-lymphocyte lineage by regulating lineage-specific transcription factors in DC progenitors, thereby contributing to DC differentiation.